Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fgene.2020.584859
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of New Stable QTLs for Grain Weight and Size by Multiple Mapping Models in Common Wheat

Abstract: Improvement of grain weight and size is an important objective for high-yield wheat breeding. In this study, 174 recombinant inbred lines (RILs) derived from the cross between Jing 411 and Hongmangchun 21 were used to construct a high-density genetic map by specific locus amplified fragment sequencing (SLAF-seq). Three mapping methods, including inclusive composite interval mapping (ICIM), genome-wide composite interval mapping (GCIM), and a mixed linear model performed with forward–backward stepwise (NWIM), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 109 publications
1
3
0
Order By: Relevance
“…Sixteen QTLs were identified in two or more individual environments, and eight genomic regions affected two or more traits (Table 1 and Table S5). Several QTLs detected for PH in this study were physically close to previously reported QTL [30,[56][57][58]. Two PH QTLs, one was 3.8 Mbp away from a PH QTL located on 4B at 611.1 Mbp, and another one was 10 Mbp away from QTL on 4B at 474.9 Mbp identified by Semagn et al [57].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Sixteen QTLs were identified in two or more individual environments, and eight genomic regions affected two or more traits (Table 1 and Table S5). Several QTLs detected for PH in this study were physically close to previously reported QTL [30,[56][57][58]. Two PH QTLs, one was 3.8 Mbp away from a PH QTL located on 4B at 611.1 Mbp, and another one was 10 Mbp away from QTL on 4B at 474.9 Mbp identified by Semagn et al [57].…”
Section: Discussionsupporting
confidence: 87%
“…The similarity of findings between Dhakal et al [29] and our study can be explained by closely related parents shared by both studies with similar genetic backgrounds. Moreover, two YLD QTLs with relatively small effects on chromosome 6D and 7B at 10.33 Mbp and 4.2 Mbp were reported by previous studies [30,[56][57][58][59].…”
Section: Discussionmentioning
confidence: 61%
“…The marker AX-95103934 linked to the QTL QTGW.iari-6B.2 exhibited a significant marker trait linkage with TGW, and the mean difference between the two allele groups was 2.35%. Similar validation for TGW on chromosomes 1B, 4B, and 7A was done by Cao et al (2020) . The marker AX-94897804 linked to QTL QDH.iari-1B can be used in breeding programs aimed at developing varieties with optimized flowering time under stress conditions, which is a key factor in determining wheat adaptation and performance under changing environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat QTL mapping and GWAS using Infinium 90 K SNP assay Drought tolerance [87] GWAS using GBS Spot blotch resistance [88] GWAS using Illumina Infinium 15 K BeadChip Head blast resistance [89] GWAS using 35 K axiom ® arrays Stripe rust resistance [90] GWAS using DArTseq technology Tan spot resistance [91] GWAS using wheat 660 K SNP array Identification of chromosomal regions of root traits [92] Haplotype-based GWAS and genotyping by sequencing Grain yield [93] QTL mapping (RIL population derived from specific locus amplified fragment sequencing (SLAF-seq)) Grain weight and size [94] GWAS using 20 K Infinitum iSelect SNP array and genomic prediction of anther extrusion in hybrid breeding…”
Section: Crop Molecular Breeding Approaches Traits Improved Referencesmentioning
confidence: 99%